Isolasi Dan Uji Aktivitas Bakteri Penghasil Selulase Asal Tanah Kandang Sapi - Albert Sembiring (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
Plant biomass from waste agricultural can be transformed to useful like bioethanol and organic fertilizer in industry and agriculture using bacterial cellulase is one alternative to convert cellulose become organic fertilizer. This research had an objective to obtain potential bacterial cellulase isolated from the soil around of cowshed in Institut Pertanian Bogor. Bacteria were isolated from soil had used serial dilution that spread in 1% Carboxy Methyl Cellulose Medium (CMC 1%) and it's incubated at 37oC for 48 hours. Qualitative test for bacteria producing cellulose was carried out by picking the selected colony in the centered of CMC medium with adding congo red 1%. Based on the results were obtained three potential isolates could produce cellulose that were KS 0.1, KS 0.7 and KS 9.1. The highest cellulolytic index is 1.33 that produced by KS 0.1. The test quantitative activity of KS 0.1 using spectrophotometry method showed that the highest of enzyme activity at the first day and lowest eighth day during incubation period. Key Words: bacteria, cellulose, soil around of cowshed